Relação peso/comprimento e fator de condição de Xiphopenaeus spp. (Decapoda: Penaeide) do Complexo Baía-Estuário de Santos/São Vicente, São Paulo, Brasil - Xavier, Juliana Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The seabob shrimp Xiphopenaeus spp. are considered the second most important fishery resource in the Southeast region of Brazil. The length-weight relationship has been used for fishing purposes, both for the interconversion between variables and for estimating the expected weight for a given size or detecting ontogenetic morphological changes related to the maturation of crustaceans and fish. Through the weight-length relationship, it is possible to obtain values referring to the condition factor, which can provide important information about the “well-being” of the species. Thus, the present study analyzed the weight/length relationship and the condition factor in Xiphopenaeus spp. in the Bay-Estuary complex of Santos/São Vicente between May 2008 and April 2009. A shrimp boat equipped with an “otter trawl” net was used to capture the shrimp. All specimens were identified as to sex and measured in relation to total length and carapace length and weight. The allometric comparison between size and weight was made using the equation y = a. xb . The results of this study revealed that there was negative allometry for males and females in which both invest more in growth in size. In the comparison of the condition factor between the sexes, the females presented a higher condition factor, indicating that they present greater energy optimization and a higher degree of adaptation to the environment.

Os camarões conhecidos como sete-barbas (Xiphopenaeus spp.) são considerados o terceiro recurso pesqueiro mais importante na região Sudeste do Brasil. A relação peso/comprimento tem sido empregada com propósitos pesqueiros, tanto para a interconversão entre variáveis, como para estimativa do peso esperado para determinado tamanho ou detecção de alterações morfológicas ontogenéticas relacionadas à maturação de crustáceos, insetos, répteis, anfíbios, peixes e mamíferos. Por meio da relação peso/comprimento é possível obter valores referentes ao fator de condição podendo fornecer informações importantes sobre o “bem estar” das espécies. Desta forma, o presente estudo analisou a relação peso/comprimento e o fator de condição em Xiphopenaeus spp. no complexo Baía-Estuário de Santos/São Vicente, entre maio de 2008 e abril de 2009. Um barco camaroneiro equipado com uma rede “otter trawl” foi utilizado na captura dos camarões. Todos os exemplares foram identificados quanto ao sexo e mensurados em relação ao comprimento total e comprimento da carapaça e pesados. A comparação alométrica entre tamanho e peso se deu utilizando a equação y = a. x^b . Os resultados desse estudo revelaram que ocorreu alometria negativa para os machos e fêmeas no qual ambos investem mais no crescimento em tamanho. Na comparação do fator de condição entre os sexos, as fêmeas apresentaram maior fator de condição indicando que apresentam maior otimização energética e maior grau de adequação no meio ambiente.
Weight/length ratio and condition factor of Xiphopenaeus spp. (Decapoda: Penaeide) of the Bay-Estuary Complex of Santos/Sao Vicente, Sao Paulo, Brazil
Keywords: Allometry; Crustaceans; Alometria; Crustaceo; Camarão; Alocação energética